PsycEXTRA Dataset 2012
DOI: 10.1037/e502412013-516
|View full text |Cite
|
Sign up to set email alerts
|

Visual Short-Term Memory Always Requires General Attention

Abstract: The role of attention in visual memory remains controversial; while some evidence suggests that memory for binding between features demands no more attention than memory for the same features, other evidence indicates cognitive costs or mnemonic benefits of explicitly attending to binding. We attempt to reconcile these findings by examining how memory for binding, features, and features during binding is affected by a concurrent attention-demanding task. We demonstrate that performing a concurrent task impairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 30 publications
(54 reference statements)
6
38
0
Order By: Relevance
“…There was also a superiority of verbal performance and special difficulty with visual information when it is followed by verbal information that also has to be retained. This same asymmetry between modalities has been reported in the adult literature (Morey & Bieler, 2013;Morey, Morey, van der Reijden, & Holweg, 2013).…”
Section: Resultssupporting
confidence: 85%
“…There was also a superiority of verbal performance and special difficulty with visual information when it is followed by verbal information that also has to be retained. This same asymmetry between modalities has been reported in the adult literature (Morey & Bieler, 2013;Morey, Morey, van der Reijden, & Holweg, 2013).…”
Section: Resultssupporting
confidence: 85%
“…Indeed, aging as well as concurrent load diminish equally short-term memory for single items and conjunctive bindings (Allen et al, , 2012Morey & Bieler, 2013), but had a larger detrimental effect on relational short-term binding than on single feature memory (Peterson & Naveh-Benjamin, 2017). Therefore, conjunctive short-term binding could be less affected by aging than relational short-term binding because older participants can more efficiently rely on automatic processes for the former.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, it seems that relational short-term binding requires a greater amount of attentional resources than conjunctive short-term binding. Indeed, while short-term memory for individual features and for conjunctive bindings are equally affected by a concurrent task Allen, Hitch, Mate, & Baddeley, 2012;Morey & Bieler, 2013), concurrent load effects are larger for relational short-term binding compared to short-term memory for single features (e.g., face-scene binding, Peterson & Naveh-Benjamin, 2017). Moreover, a direct comparison of divided attention effects on conjunctive and relational short-term binding indicated that conjunctive binding is less affected by a concurrent task, and thus can be processed more automatically, than relational binding (van Geldorp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In visual WM tests, performance has been found to be inversely related to the duration of the retention interval (Morey & Bieler, 2013;Pertzov et al, 2013;Ricker & Cowan, 2010Ricker, Spiegel, & Cowan, 2014;Shipstead & Engle, 2013; …”
Section: H1 Protection From Time-based Decaymentioning
confidence: 99%